DEMOCRATIC MANAGEMENT STYLE AND STUDENTS’ UNREST IN PUBLIC BOYS BOARDING SECONDARY SCHOOLS IN BUNGOMA COUNTY, KENYA - Andole, Beatrice; Ronald, Kikechi; Ngome, Charles Kibanani (IJRDO- Journal of Educational Research, 2023)
This study sought to find out the influence of democratic management style on students’ unrest in public boys boarding secondary schools in Bungoma County, Kenya. The study was guided by the style and behavior theory. The survey was descriptive in nature. The target population was made up of 9,993 persons comprising of 396 teachers, 9575 students and 22 Principals from 22 public boys boarding secondary schools in Bungoma County. Using Krejcie and Morgan (1970) table for determining sample sizes, the target population gave a sample size of 373 respondents. The study utilized two questionnaires i.e. for teachers and students, and interview schedules, for Principals, to collect data. Descriptive statistics and inferential statistics were used to analyse data, which was later presented in tables. Qualitative data from the Principals was analysed using the theme under study and presented in a narrative form. The study established that democratic management style had an effect on students’ unrest in public boys’ boarding schools in Bungoma County. The model coefficient was found to be positive, indicating that democratic management style had a favorable effect on student unrest. Thus the findings showed democratic management style (β = .201, p <.05) had significant effect on student unrest. Therefore principals should consider involving students in decision-making, providing opportunities for student voice and input on decisions made, and establishing clear channels of communication. Principals should foster open communication, provide opportunities for student input, and create a culture of shared decision-making.